State of the art Review for Trust Maintenance in Organizations - Fachrunnisa, Olivia; Hussain, Farookh; Chang, Elizabeth (IEEE Computer Society, 2010)
The nature of trust is dynamic rather than static. It has a life cycle or evolutionary phases. This pattern of evolutionary phase is building, maintaining and destroying. Building trust is a hard effort in every relationship. Once trust is established, it is highly need to maintain. Trust maintenance is defined as aneffort to maximizing the benefit of such trust relationship and to avoid the level of trust drop into destroying phase. In this paper, we make a general survey of the current situation of trust maintenance research. We make a brief review based on some theoretical approaches that have been used for maintain trust. Based on that review, we draw a brief conclusion to the existing status of trust maintenance research and make some suggestions for further research in this field.